Financial Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
The purpose of the paper is to use econometric methods to ascertain the main determinants of rising military expenditure in BRICS countries for the period of 1970 to 2017.The empirical result of the determinant for military expenditure of BRICS countries from 1970 to 2017 employed the panel data analysis approach. Based on the detailed theoretical and empirical literature on determinant for military expenditure, the neoclassical model was considered the best to analyzed determinant of BRICS countries military expenditure. BRICS countries political economy and security factors were incorporate for model specification. The determinant for military expenditure for BRICS include income, population, government expenditure, Security web (average military expenditure of neighboring countries within BRICS countries), internal threats and external threats. The economic, political and security factors are included. The empirical result suggest that BRICS countries military expenditure is mainly determined by its income, population, exchange rate, internal threats, inflation and political regime (proxy by democracy index). In conclusion, the result reveal that BRICS policy makers if they are interested in reversing their high unemployment and poverty rate should focus their attention on these encouraging the local production of their arms/ammunition (military industries) which will create job opportunities for their teeming youthful population. This result is in line with the findings of (Tambudzai, 2011), (Brauer, 2002) and Hartley and (Sandler & Hartley, 1995).